Advances in potato chemistry and technology - Singh, Jaspreet (Food scientist); Kaur, Lovedeep (Academic Press, 2009)
Addressing developments in potato chemistry, including identification, analysis and use of chemical components of potatoes in the development of new and innovative food and non-food products; the expert coverage includes a major focus on carbohydrate and non-carbohydrate composition, cell wall chemistry, analysis of glycoalkaloids, phenolics and anthocyanins, thermal processing and quality optimization, new and sophisticated methods of quality determination of potatoes and their products. Potato starch characteristics and its modification, nutritional and feeding value, and non-food uses of potatoes are also explored. Chapters focused on developments in post harvest storage, breeding and germplasm resources and production of potatoes with reference to industrial usage are included.